Checklist of Erotylinae (Coleoptera: Erotylidae) from Mêdog County, Xizang, China, with five new country records - Jia, Yun-Jie; Liu, Jing; Li, Jing (Zootaxa, 2026)
Fourteen Erotylinae species from Mêdog County, Xizang, China are listed. Among these, five species are newly recorded for China: Episcapha hypocrita Heller, 1918, Episcapha quadrimacula (Wiedemann, 1823), Nesitis discrepans Bedel, 1882, Aulacochilus oblongus Arrow, 1925, and Amblyopus substriatus Gorham, 1896. All fourteen species are new records for Xizang. A key and distribution map for Erotylinae species known from Mêdog County are presented. Habitus images of the newly recorded species for the country are provided. This study documents the species composition of the subfamily Erotylinae in Mêdog County, providing valuable data for biodiversity conservation efforts in southeastern Xizang.